Implementasi Punishment dan Reward dalam Meningkatkan Kedisiplinan Siswa di SDN Pakulonan 2 Kota Tangerang Selatan - Nurhasanah, Nurhasanah; Sa’odah, Sa’odah; Magdalena, Ina (ARZUSIN, 2022)
Discipline is one of the basic needs of children in the context of the formation and development of a healthy character. The goal is that children can be creative and dynamic in developing their lives in the future. Love without discipline leads to feelings of sentiment and indifference, whereas discipline without love is cruel. This study aims to determine how the application of punishment and reward in improving discipline, especially in class IVB at SDN Pakulonan 2, South Tangerang City. This research is a descriptive qualitative study by taking data at SDN Pakulonan 2, South Tangerang City with the subject and object of research being class teachers and students. Data collection techniques were conducted by interview, observation, and documentation. Data analysis was collected by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study are the teacher gives a punishment when a child commits an unfavorable act that violates the rules and regulations, and gives a reward when a child does a good action, in its application it must be in accordance with the situation and conditions so that punishment and reward are given according to needs. The forms of punishment and reward given to students are verbal and non-verbal. With the implementation of positive punishment and reward, students will learn to be better individuals than the day before.